HUBUNGAN BEBERAPA FAKTOR DENGAN PEMANFAATAN PAP SMEAR PADA WANITA PUS TAHUN 2018 - Putri Maripa Situmorang; R. Djoko Nugroho; Sri Winarni; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2020)
Data of women who take advantage of Pap smear tests has fluctuated every year, this is evidenced in 2017 women who use Pap smear tests is 0,3% compared to 2018 of 0,2%. The purpose of this study was to analyze the relationship of several factors with the use of Pap smear tests in the Kedungmundu Public Health Center in 2018. This research method uses an explanatory research type with a case control study approach. The population of this study was women of in the working area of the Kedungmundu Public Health Center as many 35.846 people with 49 case samples and 57 control samples. The research sample was taken by pair matching 1: 1 case sample using total population and control sample with purposive sampling. Data analysis included univariate (frequency distribution), bivariate (chi-square) and multivariate (logistic regression). The results showed a significant relationship of knowledge (p value = 0,001; OR = 107,2; CI = 22,254 – 516,887), health motivation (p value = 0,001; OR = 24,9; CI = 7,708 - 80,702), social culture (p value = 0,001, OR = 6,5; CI = 2,641 - 16,222), social economy (p value = 0,001; OR = 22,4; CI = 4,906 - 102,353) and family history of cancer (p value = 0,001; OR = 5,3; CI = 1,936 – 14,969) using the Pap smear test. There was no relationship between age and the use of the Pap smear test (p value = 0,113; OR = 0,518; CI = 0,228 – 1,176). It can be concluded that there is a joint influence of knowledge, health motivation and family history of cancer on the use of the Pap smear test. It is recommended for women to take part in counseling activities about the benefits of the Pap smear test.